Setting Planning Standards for Public Facilities in a City: A Case Study of Ward 50 of Dhaka City Corporation - Islam, Mohammad Atikul (Journal of Bangladesh Institute of Planners, 2012)
Availability of different types of public facilities within an urban area is required to achieve specific objectives in urban planning. Planning standards are necessary in such cases to help achieve the adequacy and quality in services and facilities. To improve the situation in rapid and unplanned growth of Dhaka city both in terms of population and size, it demands a large amount of public facilities such as open spaces, playgrounds, schools, hospitals etc. School is an important public facility that requires setting standards and choosing appropriate locations. Standard of school facilities in an area depends upon factors such as, density of population, number of per family school going children, road network etc. This paper explores the existing facilities of primary and secondary schools for school going children in Ward 50 of Dhaka City Corporation. A series of field survey were conducted in order to collect information from primary sources, and standards on school facilities were collected from secondary sources. Based on the findings, suggestions on future planning of school facilities have been made in this paper. Finally, to justify the standards for schools facilities, DMDP planning standards are followed. DOI: http://dx.doi.org/10.3329/jbip.v2i0.9577 Journal of Bangladesh Institute of Planners Vol. 2, December 2009, pp. 169-178